Widespread Crown Defoliation After a Drought and Heat Wave in the Forests of Tuscany (Central Italy) and Their Recovery—A Case Study From Summer 2017 - Pollastrini, Martina; Puletti, Nicola; Selvi, Federico; Iacopetti, Giovanni; Bussotti, Filippo (Frontiers in Forests and Global Change, 2019)
An anomalous event of drought and heat occurred in central Italy during the summer of 2017. Based on the SPI (Standardized Precipitation Index) and data from the European Space Agency, this event started in November 2016 and was characterized by a strong reduction of precipitation and soil moisture, especially in lowland areas with Mediterranean climate. The aim of this case report were to describe the impact of this event on representative forest communities in central Italy, to analyze the different responses of deciduous and evergreen tree and shrub species in contrasting environmental conditions and to assess their subsequent capacity of recovery or, if not, mortality. Trees suffered severe impacts consisting of widespread crown defoliation, leaf desiccation, crown dieback and whole tree mortality. Deciduous tree species (Fagus sylvatica, Quercus pubescens, Quercus cerris) shed their leaves during the summer, but apical buds and twigs were preserved. This allowed these species to produce new shoots in the following year (2018) and to restore the canopy closure of the stands. Mediterranean evergreen broadleaves, such as Quercus ilex and Phillyrea latifolia suffered of total or partial crown desiccation with wilting leaves and branch dieback. These species partially resprouted in 2018 from axillary and latent buds. The case presented here is discussed within the wider context of the impacts of climate change on Mediterranean forests. Future research directions should include an effective forest monitoring system that combines terrestrial and remote sensing surveys, ad hoc field climate change experiments and silvicultural trials from the perspective of proactive management for the adaptation of forests to future climatic conditions.